1976
DOI: 10.1111/j.1748-5827.1976.tb06588.x
|View full text |Cite
|
Sign up to set email alerts
|

Age changes in the eyes of the Beagle dog

Abstract: Changes with age in the eyes of Beagle dogs are described clinically and histologically. Lenticular changes involve increased prominence of the posterior lens sutures and opacity within the fetal nucleus. Cystoid degeneration of the retina was found in 85% of 8–year–old animals examined. A pigmentary change of the retina was found to be associated with focal degenerative change of the tapetum. No case of retinal atrophy was recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…We conducted a comparative and critical review of the veterinary literature that confirmed that most reports of corneal opacity or dystrophy in animals are not a heritable abnormality of cornea but represent mineralization, degeneration, edema, erosions, fibrosis, vacuolation, trauma, lipid deposition, corneal manifestations of systemic disease, postmortem change, or age-, procedure-, or treatment-related changes. 13,17,20,28,29 Using the IC3D classification system for comparison, a heritable or true corneal dystrophy with phenotypic comparability and plausible or a certain genetic basis is present in targeted mutations in mice and occurs spontaneously in several breeds of dogs and probably in Manx cats and DB rabbits. Anatomically located epithelial and subepithelial corneal dystrophies were identified in induced mutations of mice 34,36,40 and possibly Manx cats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted a comparative and critical review of the veterinary literature that confirmed that most reports of corneal opacity or dystrophy in animals are not a heritable abnormality of cornea but represent mineralization, degeneration, edema, erosions, fibrosis, vacuolation, trauma, lipid deposition, corneal manifestations of systemic disease, postmortem change, or age-, procedure-, or treatment-related changes. 13,17,20,28,29 Using the IC3D classification system for comparison, a heritable or true corneal dystrophy with phenotypic comparability and plausible or a certain genetic basis is present in targeted mutations in mice and occurs spontaneously in several breeds of dogs and probably in Manx cats and DB rabbits. Anatomically located epithelial and subepithelial corneal dystrophies were identified in induced mutations of mice 34,36,40 and possibly Manx cats.…”
Section: Discussionmentioning
confidence: 99%
“…The avascular cornea receives nutrients from the aqueous humor. [7][8][9] In nonclinical studies, corneal opacities, often reported as corneal dystrophy, are the most frequently reported spontaneous ocular finding in rabbits 10 and Sprague Dawley rats 11 and reported at various incidences depending on strain and age of rats and mice, [12][13][14][15][16][17][18] Syrian hamster, 12 Guinea pigs, 19 and beagle dogs 12,20,21 but are seldom reported in micromini-and mini-pigs 5,22,23 and cynomolgus monkeys. 24 These clinically reported opacities are sometimes associated with a variety of traumatic, environmental (light-induced), procedural (perianesthetic), metabolic/systemic (lipid), age-related or unknown events, and some may be a misdiagnosis or occasionally from drug-induced (phospholipidosis) or genetic-induced abnormalities including corneal dystrophy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These can involve the retinal pigment epithelium as well as more superficial layers of the retina. 13,29 In the retinal pigment epithelium, they are generally considered to represent the accumulation of lipofuscin. In 1 study, 13 a clinically apparent increase in pigment was noted as an age-related change, with pigment present throughout the retinal layers.…”
Section: Discussionmentioning
confidence: 99%
“…Beagle dogs revealed that 85 % of the animals were affected with cystoid degeneration of the retina. The cysts were single or multiple at or near the ora ciliaris retinae [21]. With age, the inner limiting membrane becomes thickened and increasingly vacuolated.…”
Section: Cystoid Degeneration Of the Retinamentioning
confidence: 95%